Applicability of standard delamination tests (double cantilever beam and end notch flexure) for 5HS fabric-reinforced composites in weft-dominated surface - Shiino, Marcos Yutaka [UNESP] (2015)
Currently, the standard delamination tests established by ASTM (available for mode I and mix mode) are limited to unidirectional composites. Although some researchers have conducted delamination tests in woven composites, their information is still limited. In order to understand the propagation behavior and the value of fracture toughness of woven composites, this article evaluated a 5HS carbon/epoxy composite with a weft-dominated surface. Tests were conducted in double cantilever beam and end notch flexure configurations using an energy-based approach for data reduction in modes I and II, respectively. The results were assessed in terms of delamination resistance curves (R-curves). Both delamination modes showed consistent behaviors for extending the application of the standard procedures, as the energy variation can describe well the crack growth dependence of the irregular surface caused by the crimp, which was more pronounced for mode I.